Perlakuan Air Panas dan Plant Growth Promoting Rhizobacteria untuk Menekan Cendawan Terbawa Benih pada Padi Varietas IPB-3S - Tondok, Efi Toding; Andini, Desi (Jurnal Fitopatologi Indonesia, 2023)
Hot Water Treatment and Plant Growth Promoting Rhizobacteria to Suppress Seed-Borne Fungi on Rice Variety IPB-3SIPB-3S is a new rice variety which was developed to improve national rice production in Indonesia. This study aimed to determine seed-borne fungi associated with IPB-3S variety and to determine the potential of hot water and PGPR treatment to suppress the fungal infection. The study consisted of five experiments, i.e.  seed health test by dry seed observation and by blotter test, pathogenicity test, seed treatment using hot water and plant growth promoting rhizobacteria (PGPR). Seven genera of fungi were found in IPB-3S seeds, namely Aspergillus, Penicillium, Rhizopus, Rhizoctonia, Curvularia, Fusarium and Colletotrichum. All of these fungi are pathogenic based on pathogenicity test. Seed treatment using hot water at 54 ℃ and PGPR reduced fungal infections and increased germination of IPB-3S seeds.